Optical sensing of sulfate by polymethinium salt receptors: colorimetric sensor for heparin - Bríza, Tomás; Kejík, Zdenek; Císarová, Ivana; Králová, Jarmila; Martásek, Pavel; Král, Vladimír (Chemical communications (Cambridge, England), 2008)
Polymethinium salts based on substituted malondialdehyde have been prepared; the salt with PEG substitution showed high selectivity for sulfate anions and heparin in aqueous medium at physiological condition; intracellular imaging of heparin-rich subcellular compartments was achieved with our polymethinium novel receptor for cancer cell lines.
Keywords: kolorimetrie; Models, Molecular; Salts; Sulfates; soli; Spectrophotometry; Benzothiazoles; Titrimetry; krystalografie rentgenová; Carbocyanines; Crystallography, X-Ray; heparin; molekulární modely; molekulární struktura; Molecular Structure; benzothiazoly; Heparin; Colorimetry; spektrofotometrie; titrace; karbocyaniny; sírany